Verificação in vitro da adaptação marginal de restaurações classe II utilizando resinas compostas indiretas e cerâmica odontológica - Marcos Vinicius Zuim Lara (2004)
The aim of this study was to evaluate the marginal adaptation of two aesthetic restorative materials and to compare two techniques for ceramic construction. A standard class II cavity milled in stainless steel was made. The master model was molded with polyvinilsiloxane material and Noritake Super Dental Stone was poured. The indirect composite restorations were made by an increment of 0,2g adapted on the stone model cavity walls and activated for 180 seconds. An acrylic ring was adapted around the stone model and a second increment of 0,2g of indirect composite was adapted and another 180s activation cycle was applied. The acrylic ring was removed and another cycle of activationwas made. The specimens were removed of the stone model and another 180activation cycle were applied whith the inner surface of the specimen pointed to the light. Tem specimens were made using DialogII., Vita-Zeta. and Solidex. indirect composite material. The ceramic specimens were made by duplication of stone models and pouringthe refractory die material. Twenty refractory models were made. Ten stayed at room temperature and pressure during the set and ten were submitted in a 45psi positive pressure during the set. the ceramic restorations were constructed by the refractory die materialtechnique. For the marginal evaluation, each restoration was seated in the master model with a 1,0Kgf vertical load by MP insertion gauge. All the specimens were measured ten times in an optical microscope Mitutoyo TM.. The mean of the results were submitted in ANOVA and Students t-test. There was no difference between ceramic or indirectcomposite restoration and there is no difference between the ceramic construction techniques.